Thermoresistant flagellin-adjuvanted cancer vaccine combined with photothermal therapy synergizes with anti-PD-1 treatment - Jayalakshmi Thiruppathi; Veena Vijayan; Yong Jun Bang; Hye Suk Hwang; Shee Eun Lee; Joon Haeng Rhee; Vandara Loeurng; Seol Hee Hong; Aravindkumar Sundaram; In-Kyu Park (Journal for ImmunoTherapy of Cancer)
Background Cancer immunotherapy, leveraging the immune system to target and eradicate cancer cells, has transformed cancer treatment paradigms. Immune checkpoint inhibitors (ICIs) are used in a wide array of cancers, but only a limited fraction of patients are responding. Cancer vaccines could elicit antigen-specific immune responses and establish long-term immune memory, preventing recurrence and metastasis. Despite their promising profiles, ICIs and cancer vaccines by themselves are often insufficient to overcome the immunosuppressive tumor microenvironment (TME) and recurrence/metastasis. Addressing these challenges is crucial for improving cancer immunotherapy outcomes.Methods The targeted liposomal formulation (TLIF), displaying Cyclic RGD (cRGD) peptide on the surface and encapsulating ICG and thermoresistant flagellin (FlaB) inside, was used for photothermal therapy (PTT), which was designed to induce robust immunogenic cell death (ICD) and release tumor antigens (TAs). We employed a mouse breast cancer model amenable to PTT. Utilizing a bilateral DD-Her2/neu tumor implantation model, we evaluated local and abscopal effects of combinatorial approaches employing PTT, FlaB-adjuvanted peptide vaccine (FlaB-Vax), and anti-PD-1 treatment. FlaB-Vax was designed to trigger tumor-associated antigen (TAA)-specific immune responses, which will trigger specific anti-tumor immunity. TLIF-PTT aimed to reduce tumor burden and induce ICD-mediated TA liberation for epitope spreading. Sustained anti-tumor immune memory was assessed by orthotopic rechallenging cured mice with the DD-Her2/neu tumor cells.Results The combination of TLIF-PTT and FlaB-Vax provided significantly enhanced primary tumor suppression, with strong abscopal effects and long-lasting immune memory. The addition of anti-PD-1 therapy further improved long-term relapse-free survival, highlighting the potential of this combinatorial approach to induce durable antitumor immunity and sustainably prevent cancer recurrence and metastasis.Conclusion This study demonstrates that the combination of TLIF-PTT and FlaB-Vax synergistically induced synergistic anti-tumor immune responses, which were efficaciously potentiated by anti-PD-1 treatment for recurrence-free long-term survival.